Impact of social frailty on the association between driving status and disability in older adults. (March 2022) - Doi, Takehiko; Tsutsumimoto, Kota; Ishii, Hideaki; Nakakubo, Sho; Kurita, Satoshi; Kiuchi, Yuto; Nishimoto, Kazuhei; Shimada, Hiroyuki
Highlights: This study was from 5-year longitudinal data. Driving status and social frailty were independently associated with disability. The association between driving status and disability was more pronounced in social frailty. Abstract: Introduction: The aim of this study was to investigate whether the association between driving status and disability in older adults depends on social frailty. Methods: This is a prospective study in a community setting. Participants were surveyed baseline conditions of social frailty and driving status ( n  = 4642, mean age: 71.7 years). Social frailty was defined according to criteria: going out less frequently, rarely visiting friends, feeling unhelpful to friends or family, living alone, and not talking with someone every day. Incident disability was prospectively followed up by their long-term care insurance records. Results: Of the participants, 3348 (72.1%) were current drivers. The occurrence of the social frail group, including pre-frail and frail conditions, was higher in the not driving group (55.3%) than the driving group (40.5%). The follow-up period was 60 months (mean: 56.0 months), during which 105 participants (2.3%) died, 58 participants (1.2%) moved out of the city, and 541 participants (11.7%) had incident disability. Both driving status and social frailty were associated with incident disability adjusted for covariates (not driving: hazards ratio [HR] 1.31, 95% confidence interval [CI] 1.06–1.32; social frailty: HR 1.40, 95% CI 1.17–1.67). Driving status was associated with incident disability in the social frail group (not driving: HR 1.35, 95% CI 1.03–1.77) but not in the non-social frail group (not driving: HR 1.23, 95% CI 0.86–1.74). Conclusions: Not driving and social frailty were independently associated with disability. Further, the association between driving status and disability depended on social frailty.